Self-Help Groups and Empower of Women in Delhi. - Murria, Priyanka and Verma, Satish (2013)
The successful experiences and success stories of Grameen Bank of Bangladesh has lead to recognition of microfinance through self-help groups as one of the effective tools of poverty alleviation in almost all the countries. The group approach has lead to the consideration of the SHGs as a solution for the problems of poverty and unemployment including India. This is evident from the mushroom growth of self-help groups in various states in India. The present study has been conducted in Delhi, which is to the best of the knowledge of researcher a less researched area. The study sample comprised 225 SHG members selected by multi stage random sampling procedure. In order to analyse the social impact of SHG, social empowerment indicators were identified and used in this study by following before and after approach. To find out the impact of SHGs on the SHG members, the paired t-test was applied, which is a statistical test for difference before and after joining the Self-Help Groups